Tax management as function of integrated management by the registration and tax relations of the company (Путеводитель предпринимателя)
In given article theoretical questions of essence of corporate tax management are considered, the sequence of realization of activity of corporate tax management in life cycle of the company is represented as well as the structure of management of the company taking into account corporate tax management is presented.